Racial Differences in Prostate Cancer Characteristics and Cancer-Specific Mortality: An Overview - Nobuyuki Hinata; Masato Fujisawa (The World Journal of Men's Health, 2022)
Racial differences of prostate cancer incidence and mortality among Asian, Black, and Caucasian men have been known, however, comprehensive update of this topic is not yet reported. In the present review, an overview of the racial differences in prostate cancer characteristics and cancer-specific mortality is collected and reviewed. Regarding racial differences of incidence and mortality, surprising differences in the incidence of prostate cancer are seen among different populations around the world, with some countries having rates that are 60 to 100 times higher than others. African-American men have a higher incidence of prostate cancer, higher prostate cancer mortality, and are diagnosed with prostate cancer at a younger age than Caucasian American men. Furthermore, race is gaining attention as an important factor to consider for planning active surveillance for localized prostate cancer, especially among African-Americans. In addition, the causes of these differences are being elucidated by genomic profiling. Determinants of racial disparities are multifactorial, including socioeconomic and biologic factors. Although race-specific differences in prostate cancer survival estimates appear to be narrowing over time, there is an ongoing need to continue to understand and mitigate racial factors associated with disparities in health care outcomes.